Ambalat issues: a preliminary study on the problem of indonesia territorial boundaries - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT Territory is a term to indicate an area over which right of ownership is governed exercised and which can be delimited or bounded in some way. The ownership of territory is formal and may be legally enforced. Each territory itself may be divided into a number of divisions based on two main reasons. First, it is based on empirical justification and second, it is derived by its conflict characteristic. The filtering role of boundaries and the calculus of conflict may also be used to understand the others meaning of territorial division. Ambalat issues is an urgently Indonesia territorial conflicts over sea-waters boundaries. Theoritically, Indonesia has the source of conflicts over its territorial boundary of tens neighbours countries respectively. This study attempt to observe concisely the Ambalat disputes areas over Indonesia territorial boundaries related to national sovereignty and the property rights of exploring and exploitating the mineral resources over the Exclusive Economic Zones and the Contiguous Zones.